Association between the systemic inflammatory response index and acute ischemic stroke in young people - Wang, He; Qiao, Huimin; Zhang, Xiangjian; Wu, Peng; Gao, Yuxiao; Liu, Xin; An, Haisen; Ge, Wanyue; Song, Meiling; Wang, Yatong; Wen, Ya; Yang, Yi (Frontiers in Neurology, 2025)
ObjectiveThe study aimed to explore the correlation between the systemic inflammatory response index (SIRI) and acute ischemic stroke in youth.MethodsA retrospective study was conducted. A total of 90 patients aged 18–45 years with acute ischemic stroke were included in the youth cerebral infarction (YCI) group, and 50 patients within the same age bracket without stroke or intracranial atherosclerosis, who were hospitalized during the same period, were included in the control group. Clinical information, blood biochemical indicators, and imaging data of the participants were analyzed. Binary logistic regression was used to assess the independent association between the SIRI and YCI. Furthermore, a subgroup analysis was performed on YCI patients. The subgroup classification included (i) infarct volume grouping; (ii) intracranial artery stenosis grouping; (iii) the Trial of ORG 10172 in Acute Stroke Treatment (TOAST) classification grouping; (iv) infarct distribution grouping; and (v) vasculopathy grouping.ResultsThe SIRI values were higher in the YCI group compared to the control group (p = 0.005). After adjusting for confounding factors, multivariate logistic regression confirmed that the SIRI is an independent factor associated with YCI (OR = 1.692,95% CI:1.045–2.739, p = 0.032). The receiver operating characteristic (ROC) curve showed that the optimal cutoff value for the SIRI as a predictor of YCI was 0.83*10^9/L, with corresponding sensitivity and specificity of 77.8 and 50%, respectively. The AUC was 0.643, with a 95%CI of 0.54–0.74 and a p-value of = 0.005. The subgroup analysis results were as follows: (i) There was no statistically significant difference in the SIRI values among the infarct volume groups (p = 0.633). (ii) The SIRI values in the severe stenosis group were higher than those in the non-stenosis and mild-to-moderate stenosis groups (p < 0.001). Binary logistic regression analysis showed that the SIRI was an independent associated factor for severe stenosis (original OR = 3.346,95% CI = 1.761–6.359, p < 0.001; corrected OR = 5.278,95% CI = 2.317–12.022, p < 0.001). (iii) The SIRI values in the large-vessel atherothromboembolic (LAA) group were higher than those in the small-vessel disease (SVD) group (p = 0.003). (iv) There was no statistically significant difference in the SIRI values between the infarct distribution groups (p = 0.572). (v) There was no statistically significant difference in the SIRI values between the vasculopathy groups (p = 0.345).ConclusionThe SIRI is independently associated with YCI and is significantly linked to severe intracranial arterial stenosis and the LAA subtype.